Splinting and Percutaneous Pinning Treatments of Non-Bony Mallet Finger: A Retrospective Clinical Trial - Selami KARADENİZ; Alparslan YURTBAY (Ahi Evran Medical Journal, 2023)
Purpose: Mallet finger is a common tendon injury in orthopedic practice. In this study, the clinical results of Kirschner wire (K-wire) and percutaneous pinning and splint application in patients diagnosed with non-bony mallet finger were retrospectively compared. Materials and Methods: The study included 81 patients with distal interphalangeal joint disorder within the first seven days of injury between 2011 and 2020. An extension splint was applied to 42 patients, and percutaneous pinning with K-wire was applied to 39 patients. Clinical evaluation was performed according to Crawford's mallet finger criteria. Results: The median duration of follow-up was 17 months in the splint group and 16 months in the K-wire group (p=0.632). There was no significant difference between these groups regarding the complications observed (p=0.107). The decrease in extension was significant in both groups (p<0.001 and p<0.001). There was no significant difference between the groups regarding the pre- and post-treatment extension losses (p=0.522 and p=0.085, respectively). At the end of the treatment, the degree of flexion was higher in the splint group, and the difference between the groups was significant (p<0.001). There was no significant difference between the groups regarding the assessment based on Crawford criteria (p=0.859). Conclusion: In conclusion, both conservative and surgical approaches for the treatment of mallet finger are successful, and the results are similar. Both treatment options may be offered to the patients.